2005
DOI: 10.1097/01.fpc.0000174787.92861.91
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9, CYP2C19, ABCB1 (MDR1) genetic polymorphisms and phenytoin metabolism in a Black Beninese population

Abstract: The genetically polymorphic cytochrome P450 2C9 (CYP2C9) metabolizes many important drugs. Among them, phenytoin has been used as a probe to determine CYP2C9 phenotype by measuring the urinary excretion of its major metabolite, S-enantiomer of 5-(4-hydroxyphenyl)-5-phenylhydantoin (p-HPPH). Phenytoin pharmacokinetic is also dependent on the activity of CYP2C19 and p-glycoprotein (ABCB1). To determine the influence of CYP2C9, CYP2C19 and ABCB1 genetic polymorphisms on phenytoin metabolism in a Black population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 30 publications
4
78
2
1
Order By: Relevance
“…Our investigation showed that CYP2C9*3 demonstrated significantly higher intrinsic clearance of BOS compared with wild type. Blaisdell et al (2004) demonstrated that CYP2C9*8 (R150H) exhibited a significantly increased catalytic activity in tolbutamide metabolism compared with wild-type CYP2C9*1, but Allabi et al (2005aAllabi et al ( , 2012 found CYP2C9*8 to be associated with lower clearance for phenytoin and warfarin. In the present study, we found that CYP2C9*8 showed significant decrement in V max (14.3%), which caused a lower clearance rate for BOS.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation showed that CYP2C9*3 demonstrated significantly higher intrinsic clearance of BOS compared with wild type. Blaisdell et al (2004) demonstrated that CYP2C9*8 (R150H) exhibited a significantly increased catalytic activity in tolbutamide metabolism compared with wild-type CYP2C9*1, but Allabi et al (2005aAllabi et al ( , 2012 found CYP2C9*8 to be associated with lower clearance for phenytoin and warfarin. In the present study, we found that CYP2C9*8 showed significant decrement in V max (14.3%), which caused a lower clearance rate for BOS.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limited and confusing data regarding the functional significance of these alleles. For example, CYP2C9.8 reportedly increases the metabolism of tolbutamide in vitro [23] , but reduces the metabolism of phenytoin and warfarin in vivo and/or in vitro [24,25] . Our data revealed that the CYP2C9.8 variant significantly reduced the intrinsic clearance value, while the CYP2C9.11 variant has no effect on the enzymatic activity toward tolbutamide in vitro ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Some of those CYPs exist in the form of genetic variants, which may also affect the plasma concentrations and the exposure to antiepileptic drugs. The variability of kinetic parameters of antiepileptic drugs has been reported in different populations [7][8][9][10][11][12]. There are studies on the kinetic behavior of VPA and the factors that can modify it [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 97%